Metal Sandwiches and Metal‐Matrix‐Composites Based on 3D Woven Wire Structures for Hybrid Lightweight Construction1. Issue 10 (10th July 2014) - Sennewald, Cornelia; Kaina, Steffen; Weck, Daniel; Gruhl, Andreas; Thieme, Mike; Hoffmann, Gerald; Stephani, Günter; Böhm, Robert; Cherif, Chokri; Andersen, Olaf; Kieback, Bernd; Hufenbach, Werner A.; et al.
<x xml:space="preserve">Abstract</x> Within this paper the development of 3D woven wire structures in cellular design for multifunctional multi component‐composite semi‐finished products for economically efficient and resource‐conserving processing into hybrid lightweight constructions is described. These structures can be produced in a modified weaving process and are supplied for subsequent processing such as joining and heat treatment. The developed 3D woven wire structures are predestined for the use in lightweight structures due to their high geometric variability, adjustable mechanical properties, and temperature‐resistance at a low specific weight. The structures are used as core material in sandwich construction or reinforcing material in metal matrix composites. By combining such wire structures with carbon fibers, a new class of material especially suitable for infiltration with metal matrix can be realized with outstanding high mechanical properties such as good impact and crash resistance as well as a high flexibility regarding the choice of materials and optimized structural design. Experimental investigations of mechanical properties and the failure behavior of textile based metal sandwiches and metal‐matrix‐composites with wire reinforcement have been carried out. For this purpose, extensive static and dynamic tests have been performed. The mechanical properties are compared to commercial lightweight materials of the same class as a benchmark.